Aden - Commercial Capital of Yemen : Local Economic Development Strategy - World Bank (Washington, DC, 2013)
Aden has a number of widely recognized unique assets, which are critical inputs to its emerging strategic positioning within Yemen and the region. Most notable is its natural deep-water harbor on the Red Sea, striking landscapes and distinctive topography, abundance of raw materials, and rich urban heritage. In addition, the residents of Aden are known for their hospitable nature and openness to diversity. Today, leadership in Aden, both public and private, are motivated to create prosperity. Despite a broad portfolio of assets and existence of key infrastructure, the city must address constraints that are holding back economic growth. Aden has much of the basic infrastructure required for businesses to compete, with a few areas requiring major investment. The city is spread across 6,980 square kilometers and is composed of eight districts, each with its own commercial center. The city developed on a peninsula and subsequently expanded along the coast, following the main radial route inland. The city of Aden is differentiated from the rest of the country in several important ways. First, Aden has a deep and naturally protected seaport. Second, the immediate region has an abundance of raw materials. Finally, Aden is well known for its hospitable culture and rich urban and physical heritage. These characteristics, combined with the presence of the container terminal, international airport, and Aden free zone, comprise the foundation for the future growth of the maritime, hospitality and tourism, and manufacturing industries in the governorate. Finally, the emerging institutional architecture and process for change in Aden needs further development. The quality of dialogue, particularly between the public and private sector needs to improve, and the responsibilities of the private and public sectors need to be articulated, acknowledged, and pursued. While the government needs to do everything it can to help the private sector, the businesspeople of Aden need to accept more responsibility for improving the region's economy.